PELAKSANAAN KINERJA ROOM SERVICE DI TURI BEACH RESORT BATAM - Insani, Putri; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the performance of room service employees at Turi Beach Resort Batam. A phenomenon that often occurs is that some room service employees lack initiative in serving guests. They are more concerned with the feeling of fatigue they feel due to a lot of work, so that when delivering orders to room service guests there are often delays in delivering orders. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are the Food and Beverage Manager, Food and Beverage Supervisor and Room Service employees. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded. The performance of room service employees in the food and beverage department of Turi Beach Resort Batam is quite good. This indicates that employees are trying to work optimally. This can be seen, among other things, through: the quality and quantity of employee work, neat implementation of tasks, a sense of responsibility for work, cooperative relationships between employees and superiors and co-workers. Keywords: Performance, Room Service, Turi Beach Resort Batam